Strategi Guru dalam Meningkatkan Kemampuan Berbicara Bahasa Arab di Wilayah Al Mawaddah Pondok Pesantren Nurul Jadid - Isnol Khotimah; Izzah Camalia; Ummi Kultsum; Qomariah Qomariah (KURAS Institute, 2024)
The purpose of this article is to find out the strategies used by teachers to improve Arabic speaking skills in the Arabic Language Development Program of Al Mawaddah area of Nurul Jadid Islamic Boarding School. This research is a qualitative descriptive research. Two data collection methods were used: observation and interview. The data sources studied were teachers, students, and various literatures relevant to the research object. A descriptive-analytic model was used for the data analysis. The results showed that Arabic teachers in the Al Mawaddah area of Nurul Jadid Islamic Boarding School used interactive and communicative strategies. The communicative strategy is carried out by requiring students to participate proactively in learning speaking and speaking skills. The communicative strategy requires students to understand and use communication directly from the language structure. With these two strategies, students become more communicative and better at speaking Arabic.